Isolation and Characterization of a Novel Salmonella Phage vB_SalP_TR2 - Shang, Yuting; Sun, Qifan; Chen, Hanfang; Wu, Qingping; Chen, Moutong; Yang, Shuanghong; Du, Mingzhu; Zha, Fei; Ye, Qinghua; Zhang, Jumei (Frontiers in Microbiology, 2021)
Salmonella is a widely distributed foodborne pathogen. The use of Salmonella phages as biocontrol agents has recently gained significant interest. Because the Salmonella genus has high diversity, efforts are necessary to identify lytic Salmonella phages focussing on different serovars. Here, five Salmonella phages were isolated from soil samples, and vB_SalP_TR2 was selected as a novel phage with high lytic potential against the host Salmonella serovar Albany, as well as other tested serovars, including Corvallis, Newport, Kottbus, and Istanbul. Morphological analyses demonstrated that phage vB_SalP_TR2 belongs to the Podoviridae family, with an icosahedral head (62 ± 0.5 nm in diameter and 60 ± 1 nm in length) and a short tail (35 ± 1 nm in length). The latent period and burst size of phage vB_SalP_TR2 was 15 min and 211 PFU/cell, respectively. It contained a linear dsDNA of 71 453 bp, and G+C content was 40.64%. Among 96 putative open reading frames detected, only 35 gene products were found in database searches, with no virulence or antibiotic resistance genes being identified. As a biological control agent, phage vB_SalP_TR2 exhibited a high temperature and pH tolerance. In-vitro, it lysed most S. Albany after 24 h at 37 °C with multiplicities of infection of 0.0001, 0.001, 0.01, 0.1, 1, 10, and 100. In food matrices (milk and chicken meat), treatment with phage vB_SalP_TR2 also reduced the number of S. Albany compared to that in controls. These findings highlighted phage vB_SalP_TR2 as a potential antibacterial agent for the control of Salmonella in food samples